The Aspects of Child Development on Early Childhood Education Curriculum - Dhiu, Konstantinus; Laksana, Dek Ngurah Laba (Journal of Education Technology, 2021)
Selection of learning objectives that are not quite right can affect the success of the implementation of learning, so a learning device is needed with attention to the formulation of learning objectives. This study aims to analyze learning tools regarding the learning objectives of language aspects, social emotional aspects, artistic aspects, religious and moral aspects, and physical motor aspects in the 2013 Curriculum curriculum. This type of research is a development research with the Rowntree development model. The subjects of this research are learning tools regarding the learning objectives of language aspects, social emotional aspects, artistic aspects, religious and moral aspects, and motoric physical aspects. The data collection method used in this research is to use the interview method, the questionnaire method and the documentation method. The data analysis technique used in this research is qualitative descriptive analysis technique and quantitative descriptive statistical analysis. The results of this study obtained an assessment of the learning tools developed with an average score of 4.7 by content experts, an average score of 4.3 by learning design experts, and an average score of 4.6 by linguists. The conclusion of this research is. Learning tools regarding the learning objectives of language aspects, social emotional aspects, artistic aspects, religious and moral aspects, and physical motor aspects in the 2013 Curriculum are deemed appropriate for use in early childhood learning.